Isolation and characterization of biosurfactant-producing bacteria isolated from petroleum contaminated sites with the potential to be used in bioremediation - Mohamad Zainal, Noor Shaidatul Lyana; Mohd Omar, Suhaila; Mohd Ashaaari, Mardiana (Razi Publishing, 2017)
Surfactants have been widely used to facilitate biodegradation of petroleum pollutant; particularly those are being produced by microorganisms which are also known as biosurfactant. Six bacterial isolates from petroleum contaminated sites were found to be potential hydrocarbon degrader candidates based on their ability to grow on minimal media supplemented with petroleum crude oil as sole carbon source. In addition, they also found to be having potential in producing extracellular biosurfactant based on the results of screening for biosurfactant activity. These isolates were further identified and characterized. Morphological and biochemical characteristics of these isolates have been examined and molecular identification was done by amplifying 16S rRNA gene. Three isolates were identified as the member of the genus Pseudomonas; another two isolates were the member of genus Comamonas and one isolate from the genus Stenotrophomonas. Several qualitative screening methods (microplate assay, oil displacement test, emulsification assay and drop-collapse test) showed variation of results; suggesting the need to support these findings with quantitative screening based on measurement of surface activity. BSP 6 which was found to be closely related to Comamonas aquatica was the most promising biosurfactant producer found in this study based on two positive results out of four qualitative screening methods performed.